3D Graphene Hollow Nanospheres@Palladium‐Networks as an Efficient Electrocatalyst for Formic Acid Oxidation. Issue 18 (28th September 2015) - Qiu, Xiaoyu; Wu, Ping; Xu, Lin; Tang, Yawen; Lee, Jong‐Min
Abstract : Graphene has served widely as a support material for noble metal nanoparticle electrocatalysts in fuel cells. During the synthesis of electrocatalysts, however, the intense stacking and folding of graphene nanosheets decreases the utilization and activity of electrocatalysts, owing to the following aspects: i) the noble metal wrapped by the winding graphene cannot be fully utilized; ii) the structural destruction of graphene decreases the specific surface area and increases electrical resistance; and iii) the hydrophobicity and wrinkles of graphene greatly increase the mass transfer resistance of fuel molecules and electrolytes. In this work, 3D graphene oxide hollow nanospheres are designed to minimize wrinkles, maximize specific surface area, and realize the regular clipping of 2D graphene oxide. The 3D‐reduced graphene oxide hollow nanosphere supported Pd‐network nanohybrids (3D‐RGO/Pd‐NWs) are then obtained using 3D graphene oxide hollow nanospheres as a reaction precursor. The skeleton of 3D‐RGO not only acts as an exclusive inner conducting shell to promote electron and ion kinetics but is also crucial for enhancing the permeation of fuel molecules and electrolytes. Therefore, 3D‐RGO/Pd‐NWs exhibit enhanced electrocatalytic activity and durability for the formic oxidation reaction in an acidic medium compared to 2D graphene supported Pd nanoparticles and commercial Pd/C electrocatalysts. Abstract : An electrocayalyst with graphene supported Pd nanoparticles is constructed with three‐dimensional reduced graphene oxide hollow nanospheres for the first time. The skeleton of three‐dimensional reduced graphene oxide not only acts as an exclusive inner conducting shell to promote electron and ion kinetics, but is also crucial for enhancing the permeation of fuel molecules and the electrolyte.